Changing institutional landscape and transportation development in Dhaka, Bangladesh - Rakibul Ahasan; Md. Nazmul Hoda; Md. Shaharier Alam; Yead Rahman Nirzhar; Ahsanul Kabir (Heliyon, 2023)
Cities in the global south, constrained by limited resources, face challenges in delivering efficient transportation infrastructure and services to support their rapidly growing urban populations. Dhaka, serves as an example, as it grapples with the increasing demand driven by population growth, exacerbated by factors like land and resource scarcity, as well as intricate geopolitical dynamics. Despite the construction of a metro rail and other similar mass transit options, Dhaka continues to face difficulties in meeting the increasing transportation demand, posing a persistent challenge. Multiple institutions, including a coordination authority, are working to provide improved transportation services by implementing diverse strategic approaches focusing on infrastructure development, and formulating policies aimed at facilitating better mobility and accessibility. Over the past fifty years, the institutional arrangement and roles within the transportation system have changed. This study examines the institutional arrangements and how they have evolved, along with reviewing transportation development policies during this period. The findings indicate the involvement of multiple organizations in the city's transportation system performing distinct activities–– administrative, coordinating, legislative, regulatory, construction and management, and law enforcement. These authorities often encounter challenges fulfilling their responsibilities stemming from differences in vision, organizational structure, jurisdiction and most notably, lack of coordinatoon, resulting in ineffective infrastructure development and duplicated activities. To improve the transportation system, this study recommends better equipping the existing coordinating authority and expanding its jurisdiction to include other institutions. This approach aims to enhance coordination and address the challenges faced by Dhaka's transportation system, ultimately facilitating improved mobility and accessibility for the city's growing population.